1971
DOI: 10.1002/1097-0142(197109)28:3<692::aid-cncr2820280326>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Minute pulmonary chemodectoma

Abstract: The minute chemodectomas of the lung belong to the paraganglioma group of neoplasms, which include carotid and aortic body tumors. They are frequently multiple, small in size, and are nearly always detected fortuitously on histologic examination of sections of a lung taken from an older patient. They are believed to arise from the normal chemoreceptors of the lung. There is no indication that these small neoplasms are functional. It has been proposed that pulmonary chemodectomas may be induced by pulmonary thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1975
1975
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…The low proliferative fraction and the lack of mitotic figures or cellular atypia suggest that these lesions are benign, slow-growing proliferations of arachnoid-like cells, although their reactive of neoplastic nature is still debated. A polyclonal origin of MNs has been recently proposed [13], and their higher prevalence in patients with thromboembolic disease, cardiac failure and various chronic pulmonary diseases with scarring, as well as in inhabitants of highaltitude regions, support the view that these lesions may represent hyperplastic growths induced by local hypoxia rather than true neoplasms [5,9,16]. Epidemiological data also support a reactive nature for pulmonary MNs.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The low proliferative fraction and the lack of mitotic figures or cellular atypia suggest that these lesions are benign, slow-growing proliferations of arachnoid-like cells, although their reactive of neoplastic nature is still debated. A polyclonal origin of MNs has been recently proposed [13], and their higher prevalence in patients with thromboembolic disease, cardiac failure and various chronic pulmonary diseases with scarring, as well as in inhabitants of highaltitude regions, support the view that these lesions may represent hyperplastic growths induced by local hypoxia rather than true neoplasms [5,9,16]. Epidemiological data also support a reactive nature for pulmonary MNs.…”
Section: Discussionmentioning
confidence: 91%
“…In fact, a prevalence of one MN in every 200-300 unselected autopsies has been reported [3,10], and our findings of 11 such nodules in 6 of 540 patients with lung cancer is consistent with the above figures. The prevalence of MNs can still increase significantly to approximately one in 25 autopsies, if a specific search is made, especially in case of pulmonary embolism, cardiovascular disease and lung cancer [3,9,16]. Unfortunately, the 546 invariable expression of progesterone receptors does not help clarifying whether these lesions are reactive or neoplastic in nature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Minute pulmonary meningothelial-like nodules (MPMNs) consist of epithelioid cell nests or whorls in a "Zellballen"-like arrangement centered on small veins [1][2][3]. From their architecture, cytologic characteristics, and relationship with vessels, MPMNs were believed to have an oxygenmonitoring function, as a chemoreceptor, so Korn et al [3] reported these lesions as "pulmonary chemodectoma" in 1960.…”
Section: Introductionmentioning
confidence: 99%
“…The patient population shows a marked female predominance. There appeared to be an association with specific conditions such as cardiac failure, chronic bronchitis and emphysema, thromboembolism and malignancy (3,5). They are uncommon, tumor-like lesions found in the pleura or parenchyma of the lung as solitary or multiple nodules.…”
Section: Introductionmentioning
confidence: 99%